PERLINDUNGAN HAK ANAK DALAM PERCERAIAN MENURUT HUKUM KELUARGA ISLAM - Muhammad Husni Abdulah Pakarti (Program Studi Hukum Keluarga Islam, 2023)
This study aims to examine the protection of children's rights in cases of divorce according to Islamic family law. Divorce is a problem that often occurs in family life and can have a negative impact on children. Therefore, it is important to understand how Islamic family law provides protection for children's rights in the context of divorce. Normative legal research methods with a literature study approach. The data used are relevant legal materials, including the Al-Qur'an, hadith, as well as the opinions of Islamic scholars and jurists regarding issues of divorce and protection of children's rights. The results of this study indicate that Islamic family law pays great attention to the protection of children's rights in divorce cases. Islamic law emphasizes the importance of maintaining the integrity of the family and the well-being of children as a top priority. In the context of divorce, Islamic law places a great responsibility on both parents to protect the rights of the child, including the rights to life, education, health and security. In addition, Islamic family law also provides clear guidelines regarding divorce procedures and children's rights after the divorce occurs. In terms of child care, Islamic law encourages parents to reach a good and fair agreement in the best interest of the child. If there is no agreement, the judge will decide on child care based on the principles of fairness and the best interests of the child.